Air detection of monkeypox virus in a dedicated outpatient clinic room for monkeypox infection diagnosis. Issue 3 (March 2023) - Mellon, Guillaume; Rubenstein, Emma; Antoine, Meghann; Ferré, Valentine Marie; Gabassi, Audrey; Molina, Jean-Michel; Delaugerre, Constance; LeGoff, Jérôme
Abstract: Background: The World Health Organization (WHO) reported an outbreak of monkeypox virus (MPXV) in Western countries on May 12 th, 2022. In early October, WHO counted 68 900 cases in the world outside Africa. MPXV spreads all around the environment of infected patients through direct contact with lesions, body secretion, or liquids. Interrogations about MPXV spreading through respiratory secretions have been reported but appear bewildering. Thus, we investigated for virus identification in the air around infected patients to move forward with unresolved questions. Methods: We collected air samples using the AerosolSense™ device in a dedicated room where monkeypox suspected patients were examined in our quaternary hospital's outpatient infectious disease clinic. Samples were analyzed with a MPXV PCR to determine the presence of viral DNA in the air. Results: The study took place from July 26 th to August 5 th, 2022. We obtained seven four-hours-bioaerosol samples during the study period. Over the seven sessions sampled, six air samples were positive with a median Ct value of 36 (min-max: 32.0 – 38.0). Forty patients were present during the investigation; 17 (43%) were diagnosed monkeypox positive; 13 clinically and four virologically with a median Ct of 21 (min-max: 18.0 – 35.0). During the session, where no patients were diagnosed with monkeypox, air collection was also MPXV negative. Conclusion: This investigation reports the presence of MPXV DNA in air samples collected in a room dedicated to monkeypox-infected patients' examination and testing. Thus, we highlight the importance of personal protective equipment worn by consulting patients and healthcare workers and surface decontamination to avoid infection transmission.